Ecotourism and health tourism in the Caribbean - Grell, Gerald A.C. (UWI Cave HillBB, 1993)
Sees the region as having a great potential for ecotourism, however the environment must be preserved and concept of sustainable development must be central to the success of such ventures. Acknowledges that the region has particular advantages in health and tourism and this should be part of the ecotourism investment package.